Komparasi Studi Fenomenologi dalam Penyelesaian Sengketa Harta Warisan Ditinjau dari Perspektif Kompilasi Hukum Islam dan Undang-Undang Perkawinan di Indonesia - Iswandi, Andi (Qonuni: Jurnal Hukum dan Pengkajian Islam, 2023)
This study compares the phenomenological approach in resolving inheritance disputes, with a focus on the views of the Compilation of Islamic Law and the Marriage Law in Indonesia. This study uses the phenomenological method to explore the experiences and meanings given by individuals or groups regarding the settlement of inheritance disputes. The results showed that the majority of participants had a strong understanding of the provisions of Islamic law and marriage laws in the context of inheritance distribution. They tend to believe that resolving inheritance disputes based on Islamic law is fairer than civil law. The role of the mediator is considered very crucial, and participants feel it is important to make settlement procedures more accessible and understandable to the community. The conclusion of this study shows that a strong understanding of Islamic law and marriage laws can affect the outcome of inheritance dispute resolution. Furthermore, giving the role of mediator and efforts to increase accessibility and public understanding of settlement procedures can increase the effectiveness of resolving inheritance disputes in Indonesia. This research provides additional insight into the dynamics of resolving inheritance disputes in the context of Islamic law and civil law in Indonesia.